"That simply cannot be allowed to happen". The Western Sydney Wanderers and the paradox of Australian soccer. (17th November 2022) - Hale, Adrian
ABSTRACT: The game of soccer in Australia is a paradox for many reasons. While soccer enjoys an enormous following as one of Australia's largest amateur participation sports at the junior levels, the professional version of the game struggles for media attention in an otherwise very sports-oriented nation. In addition, while it could be described as pan-ethnic in that it has a popular participation rate across most communities, and while it has strong links to Australia's British heritage and the origins of the game itself, soccer today is largely viewed as un-Australian, 'existing on the margins of the Australian Anglophone sporting mainstream' because of its 'post-war history of association with ethnic communities of non-English speaking background'.